2018
DOI: 10.3390/nu10060666
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Antagonists and Cognitive Decline in Older Adults: A 24-Month Follow-Up

Abstract: Vitamin K participates in brain physiology. This study aimed to determine whether using vitamin K antagonists (VKAs), which interfere with the vitamin K cycle, were (i) cross-sectionally associated with altered cognitive performance, and (ii) independent predictors of cognitive changes in older adults over 24 months. Information was collected on the use of VKAs (i.e., warfarin, acenocoumarol, and fluindione) among 378 geriatric outpatients (mean, 82.3 ± 5.6 years; 60.1% female). Global cognitive performance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The same author found an important decline in executive functions (assessed with frontal assessment battery) among geriatric patients treated with VKAs over at 24 months follow up. It's worth noticing how, in the same study, decline in Mini mental state examination (MMSE) scores, used as an assessment of cognitive performance, was not found significantly associated with VKAs use over the same period of time ( 72 ).…”
Section: Vitamin K and Cognitive Declinementioning
confidence: 96%
“…The same author found an important decline in executive functions (assessed with frontal assessment battery) among geriatric patients treated with VKAs over at 24 months follow up. It's worth noticing how, in the same study, decline in Mini mental state examination (MMSE) scores, used as an assessment of cognitive performance, was not found significantly associated with VKAs use over the same period of time ( 72 ).…”
Section: Vitamin K and Cognitive Declinementioning
confidence: 96%
“…Increased VK intake was linked with fewer and less severe subjective memory disorders in participants taking no VK antagonists (VKAs) [183]. The use of VKAs as anticoagulant medications lowered the VK bioavailability, thus reducing the VK concentration and increasing the altered cognitive performance risk and the frequency of cognitive impairment in the elderly [184,185].…”
Section: The Effect Of Vitamin K On Neurodegenerative Diseasesmentioning
confidence: 99%
“…Another study from the same group found more severe executive dysfunction at baseline and incident executive decline over 1 year among 46 geriatric patients using VKAs, when compared with their counterparts (n = 332). 124 Taking such findings into consideration, it is bestowed upon future comparative trials to explore for any differential effect of the newer NOACs on cognition in patients with AF. It should be noted that the latter 2 studies did not provide any data on TTR.…”
Section: Preventive Interventionsmentioning
confidence: 99%